Usage des technologies et investigation en mathématiques : quels contrats didactiques possibles ? - Ghislaine Gueudet; Marie-Pierre Lebaud (Recherches en Éducation)
Mathematics didactics invites to consider inquiry-based teaching as a particular form of didactic contract, leaving an important responsibility to the students, regarding the knowledge at stake and its evolution in class. Does the use of technology support the development of such a contract? Under which conditions, concerning the mathematical situations, or the role of the teacher, or the use of technology? In this article, we discuss these questions, drawing on the literature, and on different research projects concerning mathematics at secondary school. We analyze the contract, considering how the teacher and the students share the responsibility concerning three dimensions: posing initial questions, producing answers, advancing knowledge.